FGIC Corruption Barometer - Hasnah, Haron; Ishak, Ismail; Daing Nasir, Ibrahim; Yuserrie, Zainuddin; Mohd Ridzuan, Darun; Suhaidah, Hussain; Aziman, Abdullah; Fernando, Yudi; Akhtar, Satar; Raziman, Abdullah Hashim (Penerbit UMP, 2019)
HASNAH HARON, ISHAK ISMAIL, DAING NASIR IBRAHIM, YUSSERIE ZAINUDDIN, MOHD RIDZUAN DARON, SUHAIDA HUSSAIN, AZIMAN ABDULLAH, YUDI FERNANDO, AKHBAR SATAR & RAZIMAN ABDULLAH HASHIM